2013
DOI: 10.1002/2012gb004536
|View full text |Cite
|
Sign up to set email alerts
|

National‐scale estimates of forest root biomass carbon stocks and associated carbon fluxes in Canada

Abstract: Canada's forests play an important role in the global carbon cycle through carbon (C) storage and C exchange with the atmosphere. While estimates of aboveground biomass have been improving, little is known about belowground C storage in root biomass. Here we estimated the contribution of roots to the C budget of Canada's 2.3 × 106 km2 managed forests from 1990 to 2008 using the empirical modeling approach of the Carbon Budget Model of the Canadian Forest Sector (CBM‐CFS3) driven by detailed forestry data sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 84 publications
(125 reference statements)
1
14
0
Order By: Relevance
“…Our biomass C stock estimates for riparian woodlots also fall in the range of mean biomass C stock estimates for managed forests of the Mixedwood plains ecozone (Stinson et al, 2011). Furthermore, our belowground (root) biomass C stock amounts for poplar buffers (4.8e13 t/ha) and riparian woodlots (5.2e36.8 t/ha) (Table 3) are in the same order of magnitude than national scale estimates for managed forests of Eastern Canada, which are 10e17.5 t/ha (Smyth et al, 2013).…”
Section: Carbon Stocks In the Different Riparian Vegetation Cover Typessupporting
confidence: 51%
“…Our biomass C stock estimates for riparian woodlots also fall in the range of mean biomass C stock estimates for managed forests of the Mixedwood plains ecozone (Stinson et al, 2011). Furthermore, our belowground (root) biomass C stock amounts for poplar buffers (4.8e13 t/ha) and riparian woodlots (5.2e36.8 t/ha) (Table 3) are in the same order of magnitude than national scale estimates for managed forests of Eastern Canada, which are 10e17.5 t/ha (Smyth et al, 2013).…”
Section: Carbon Stocks In the Different Riparian Vegetation Cover Typessupporting
confidence: 51%
“…Process-based ecosystem models employ biogeochemical processes, including photosynthesis, absorption, and carbon allocation. The models generally couple biology, soil, climate, hydrology, and anthropogenic effects (Smyth et al 2013). Constraints in data source (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We did not separate fine and coarse roots in this procedure. Because previous studies demonstrated that coarse roots, which have longer residence time than fine roots, made the predominant contribution to root biomass (IPCC 2006;Miller et al 2006;Bijak et al 2013;Smyth et al 2013), we assumed that disregarding fine and coarse roots is acceptable in terms of quantifying the total root biomass.…”
Section: Below-ground Biomassmentioning
confidence: 99%